English Students’ Teaching Skills Applied in Micro Teaching Class at the 5th Semester of Panca Sakti University Bekasi - Rusmiati, Yanti (Samudra Publisher, 2026)
Microteaching plays an important role in preparing pre-service English teachers to develop essential teaching skills before engaging in actual classroom practice. This study aimed to describe and analyze the teaching skills demonstrated by fifth-semester students of the English Education Study Program at Panca Sakti University Bekasi during a Micro Teaching course. The study employed a descriptive design combining quantitative descriptive and qualitative analyses. The participants were 16 fifth-semester students enrolled in the Micro Teaching course during the 2024/2025 academic year. Data were collected through structured observations of students’ microteaching performances and semi-structured interviews. Observation data were analyzed using percentages to describe the application of each teaching skill, while interview data were analyzed through data organization, coding, categorization, and interpretation to complement the observation findings. The results revealed variations across the ten teaching skills examined. The use of teaching media achieved the highest percentage (95%), followed by explaining (82%), opening (78%), and variation skills (75%). In contrast, small-group discussion showed the lowest percentage (20%), followed by organizing small-group and individual work (43%) and reinforcement skills (48%). These findings indicate that the students demonstrated stronger teacher-directed instructional skills than interactive and learner-centered teaching skills. Therefore, microteaching should provide more structured opportunities for repeated practice, feedback, and reflection to strengthen interactive teaching skills and promote a more balanced development of pre-service English teachers’ teaching competence.